Advanced X-ray Detector Technologies Design and Applications - Iniewski, Krzysztof (Kris).; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
TThis book offers readers an overview of some of the most recent advances in the field of detectors for X-ray imaging. Coverage includes both technology and applications, with an in-depth review of the research topics from leading specialists in the field. Emphasis is on high-Z materials like CdTe, CZT and perovskites, since they offer the best implementation possibilities for direct conversion X-ray detectors. Authors discuss material challenges, detector operation physics and technology and readout integrated circuits required to detect signals processes by high-Z sensors.
Introduction to High-Z Semiconductor Detectors -- High-Z compound semiconductors as sensors for hybrid pixel area detectors -- Photon-integrating hybrid pixel array detectors for high-energy x-ray applications -- Photon counting detectors and their applications in medical imaging -- CZT Detectors for High-Flux -- Position-sensitive virtual Frisch-grid CdZnTe detectors and their applications -- Drift detectors and Compton cameras -- CdTe Pixel Detectors for Hard X-Ray Astronomy -- High-Z pixel sensor characterization for synchrotron applications -- High Performance CdTe/CZT Spectro-Imagers.
Keywords: Electronic circuits; Signal processing; Electronic Circuits and Systems; Electronic Circuits and Systems; Digital and Analog Signal Processing; Detectors; X-rays